2011
DOI: 10.1111/j.1467-7687.2010.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐month‐olds privilege words over other linguistic sounds in an associative learning task

Abstract: We examined whether 12-month-old infants privilege words over other linguistic stimuli in an associative learning task. Sixty-four infants were presented with sets of either word–object, communicative sound–object, or consonantal sound–object pairings until they habituated. They were then tested on a ‘switch’ in the sound to determine whether they were able to associate the word and/or sound with the novel objects. Infants associated words, but not communicative sounds or consonantal sounds, with novel objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 30 publications
3
77
5
Order By: Relevance
“…Infants treat others’ speech and non-speech as functionally distinct when categorizing (Balaban & Waxman, 1997; Ferry, Hespos, & Waxman, 2010; Fulkerson & Waxman, 2007), labeling (Mackenzie, Graham, & Curtin, 2011), and individuating (Xu, 2002; Xu, Cote, & Baker, 2005) objects. Infants also use speech to identify potential communicative partners and learn from communicative interactions.…”
mentioning
confidence: 99%
“…Infants treat others’ speech and non-speech as functionally distinct when categorizing (Balaban & Waxman, 1997; Ferry, Hespos, & Waxman, 2010; Fulkerson & Waxman, 2007), labeling (Mackenzie, Graham, & Curtin, 2011), and individuating (Xu, 2002; Xu, Cote, & Baker, 2005) objects. Infants also use speech to identify potential communicative partners and learn from communicative interactions.…”
mentioning
confidence: 99%
“…The design of Experiment 1 was based on a task in which older infants have failed to learn labels without some form of supplemental support (Graf Estes et al, 2007; Graf Estes & Hurley, 2013; Hay, Pelucchi, Graf Estes, & Saffran, 2011). There is evidence from other variations of the Switch task that 14-month-olds (Byers-Heinlein et al, 2013; Werker et al, 1998), and even younger infants (12-month-olds; MacKenzie et al, 2012; MacKenzie et al, 2011) can learn phonetically distinct object labels, but the task has revealed vulnerabilities in learning as well. For example, Werker et al (1998) reported that 14-month-olds only displayed learning when objects moved during labeling, not when they were stationary.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence is even more mixed in younger infants. Werker et al (1998) found that 12-month-olds failed to learn object labels in the Switch task, but MacKenzie and colleagues (MacKenzie, Curtin, & Graham, 2012; MacKenzie, Graham, & Curtin, 2011) have reported successful learning of other labels at this age. A series of experiments from Hollich and colleagues (2000; Experiments 4-9) suggested that 12-month-olds require multiple social-referential cues during labeling to learn new object names, cues that are absent in the Switch task.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, several studies have shown that infants, even pre-babblers, readily associate heard “words” with referents, and use these symbols to categorize objects or parts of objects (see Fulkerson and Waxman, 2007; Ferry et al, 2010, and for children of 12 months, MacKenzie et al, 2011). Interestingly, the reports also show that infants are less successful in forming symbolic associations when presented with sounds like intoned [mmm] or sounds that cannot be articulated, and instead attend to familiar speech (MacKenzie et al, 2011; Marno et al, 2015, 2016; and for evidence that activity in language areas of the brain are organized in terms of speech sounds, see Magrassi et al, 2015). This ability to acquire symbols is not distinctly human, as we noted, but communication by way of orally articulated signs is.…”
Section: Discussionmentioning
confidence: 99%